Simultaneous Determination of Picroside I and II Using High Performance Liquid Chromatography - Chen, Haifeng; Pan, Yu; Ding, Xiong; Liu, Xiaoli (Asian Journal of Chemistry, 2014)
Rhizoma Picrorhizae is the dried rhizomes of Picrorhiza scrophulariaeflora Pennelland has been used in Chinese medicine for treating fever, liver disorders and jaundice for over a thousand years. The objectives of this research were to determine whether the different regions could result in different quality by determining the content of picroside I and II in different samples. A modified HPLC method using a diode array detector (DAD) has been developed and ten samples of P. scrophulariaeflora from eight different regions were evaluated. The results showed that the samples collected from Yunnan in the content of picroside II are higher but lower in the content of picroside I, comparing with the samples collected from Tibet.